The environmental characteristics and phenotypic diversity of Asian swamp eel Monopterusalbus (Zuiew, 1793) from Bangka Belitung islands as basic for aquaculture developments - Ahmad Fahrul Syarif (Journal of Aquatropica Asia, 2016)
The research aimed to analized the environmental characteristics and toevaluate the phenotypes diversity of asian swamp eel from Bangka Belitung islands for basic aquaculture developments.Samples of Asian swamp eel catches were collected from three locations Rias, Bencah and Balunijuk. All of catches was measured by truss morphometrics and sexual distributions.Water quality measurements was conducted in situ at each sample location. The results showed that there is close relationship betweenasian swamp eel population of Bencah and Balunijuk based on similarities of their phenotypic diversity, but not with population from Rias. It showed that Asian swamp eel from Bencah and Balunijuk is potential to be cultured, but it must be adjusted with the conditions of physical-chemical variabel of each locations for the best adapted to culture.